Pengaruh Kompetensi Aparatur Desa dan Tingkat Pendidikan Terhadap Kualitas Laporan Keuangan Desa: Studi pada Desa-desa di Kecamatan Lemito, Kabupaten Pohuwato, Provinsi Gorontalo - Refky Tooy; Harun Blongkod; Ikhlas UL Aqmal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to analyze the influence of village apparatus competency and education level on the quality of village financial reports. Transparency, accountability and community participation in village financial management are important aspects in realizing good financial governance. However, various factors such as low competency of village officials and lack of relevant educational background can affect the quality of village financial reports. The research method used is a quantitative approach with data analysis techniques using Structural Equation Modeling (SEM) via AMOS software. The research sample consisted of village officials in Lemito District, Pohuwato Regency, Gorontalo Province. The research results show that the competence of village officials has a positive and significant effect on the quality of village financial reports with a t-value of 3.740 (p < 0.05). Likewise, the education level of village officials has a positive and significant influence on the quality of village financial reports with a t-value of 2.149 (p < 0.05). Simultaneously, village apparatus competency and education level explain 76.5% of the variation in the quality of village financial reports. These findings support agency theory which emphasizes the importance of accountability and transparency in village financial governance. Increasing the competence and education of village officials is a key factor in producing financial reports that are accurate, transparent and accountable. Therefore, the recommendation of this research is the need for training programs and increasing the capacity of village officials in the field of accounting and financial management in order to improve the quality of village financial reports.